Pengaruh E-Booklet tentang Mp-Asi dengan Responsive Feeding Terhadap Pengetahuan dan Sikap Ibu Hamil dalam Program Pencegahan Stunting - Romadhoni, Hasriyanti; Erismawati, Erismawati (Universitas Malahayati, 2025)
ABSTRACT Stunting or short toddlers is one of the main concerns regarding nutritional problems experienced by toddlers in the world today, this problem can have a serious impact on the quality of human resources in the future. The average prevalence of stunting in children under five in Indonesia is 37.2 percent. Meanwhile, the prevalence in other Southeast Asian countries such as Thailand is 16%, Vietnam 23% and Myanmar 35%. Stunting incidents that occur in toddlers can have short, medium to long term impacts. The causes of stunting are due to inadequate nutritional needs, infections and parenting patterns. One of the efforts to increase mothers' knowledge and attitudes in prevention is providing education about MP-ASI and Responsive feeding. The educational media that can be used is E-Booklet. E-booklet educational media is an educational media innovation that is simpler than an e-book (electronic book) which is created as an electronic document and can be read using software such as a computer, laptop, tablet or smartphone.The aim of this research is to determine the effect of the E-Booklet about MP-ASI with Responsive Feeding on the knowledge and attitudes of pregnant women in the stunting prevention program at the Amban Community Health Center. The type of research is quasi-experimental research with a pretest and posttest control group research design. This research was divided into 2 groups, namely the intervention group and the control group. The research sample consisted of 40 pregnant women in the pregnant women's class in the Amban Community Health Center working area, divided into 20 pregnant women in the control group and 20 pregnant women in the experimental group.The results show that there is a difference in the scores of the intervention group before and after giving the e-booklet with a p-value <0.05, which means there is a moderate difference in the control group before and after treatment, there is no difference with a p-value>0.05. Keywords: Attitude, Knowledge, MP-ASI, Responsive Feeding ABSTRAK Stunting atau balita pendek menjadi salah satu perhatian utama masalah gizi yang dialami oleh balita di dunia saatini, permasalahan ini dapat berdampak serius pada kualitas sumber daya manusia nantinya. Prevalensi rata - rata stunting pada anak balita di Indonesia adalah 37,2 persen. Sedangkan untuk prevalensi negara Asia Tenggara lainnyaseperti Thailand 16%, Vietnam 23% dan myanmar 35%. Kejadian stunting yang terjadi pada balita dapat berdampak dalam jangka pendek, menengah hingga Panjang. Penyebab terjadinya kejadian stunting diakibatkan karena tidak tercukupinya kebutuhan gizi, adanya infeksi serta pola pengasuhan. Salah satu upaya սոtսk meniոgkatkaոpengetahuan serta sikap ibu daӏam peոcegahaո stսոtiոg yaitս memberikan edukasi mengenai MP-ASI sertaResponsive feeding. Media edukasi yang dapat digunakan yaitu E-Booklet. Media edukasi e-booklet merupakan sebuah inovasi media edukasi yang berbentuk yang lebih sederhana dari e-book (electronic book) yang dibuatsebagai dokumen elektonik dan dapat dibaca menggunakan perangkat lunak seperti komputer, laptop, tablet, atausmartphone. Tujuan dalam penelitian ini untuk mengetahui pengaruh E-Booklet tentang MP-ASI dengan responsiveFeeding terhadap pengetahuan dan Sikap Ibu Hamil dalam program pencegahan stunting di Puskesmas Amban. Jenispenelitian adalah penelitian quasy eksperimen dengan desain penelitian control grup pretest dan posttest. Penelitianini terbagi menjadi 2 kelompok yaitu kelompok intervensi dan kelompok kontrol. Sampel penelitian merupakan ibuhamil yang berada di kelas ibu hamil pada wilayah kerja Puskesmas Amban berjumlah 40 orang yang terbagi dalam 20ibu hamil pada kelompok control dan 20 ibu hamil pada kelompok eksperimen. Hasil menunjukan bahwa terdapat perbedaan skor kelompok Intervensi sebelum dan setelah pemberian e-booklet dengan nilai p-value<0,05 yang berarti ada perbedaan sedang pada kelompok kontrol sebelum dan sesudah perlakuan tidak ada perbedaan dengan nilai p-value>0,05. Kata Kunci: Sikap, Pengetahuan, MP-ASI, Responsive Feeding